Influence Artificial Intelligence To Customer Experiences (Study On DRAIV Users in Tual, Maluku) - Marasabessy, Nabila Cecilia (Management Studies and Business Journal (PRODUCTIVITY), 2024)
Artificial intelligence (AI) technology gives marketers the ability to identify differences between consumers, understand various personas, and understand the factors that drive consumers to make purchasing decisions. Therefore, marketers use Artificial Intelligence to recognize and predict consumer habits. Information obtained from AI, marketers can provide a special experience for each consumer. The objective of this study is to determine and measure the impact of AI on customer experience using simple regression analysis. There are four AI indicators analyzed, namely mechanical intelligence, analytical intelligence, intuitive intelligence, and empathetic intelligence. In addition, there are four dimensions of customer experience that are evaluated, namely immersion, flow, cognitive fit, and emotional fit. From the results of observations of 116 people, it was concluded that Artificial Intelligence and Draiv's customer experience received a positive assessment, and Artificial Intelligence had a significant effect on customer experience.